Development and Selection of the Human Vγ9Vδ2+ T-Cell Repertoire - Willcox, Carrie R.; Davey, Martin S.; Willcox, Benjamin E. (Frontiers in Immunology, 2018)
Vγ9Vδ2+ lymphocytes are among the first T-cells to develop in the human fetus and are the predominant peripheral blood γδ T-cell population in most adults. Capable of broad polyclonal responses to pyrophosphate antigens (pAg), they are implicated in immunity to a diverse range of infections. Previously Vγ9Vδ2+ development was thought to involve postnatal selection and amplification of public Vγ9 clonotypes in response to microbial stimuli. However, recent data indicate the Vγ9Vδ2+ T-cell receptor (TCR) repertoire, which is generated early in gestation, is dominated by public Vγ9 clonotypes from birth. These chains bear highly distinct features compared to Vγ9 chains from Vδ1+ T-cells, due either to temporal differences in recombination of each subset and/or potentially prenatal selection of pAg-reactive clonotypes. While these processes result in a semi-invariant repertoire featuring Vγ9 sequences preconfigured for pAg recognition, alterations in TCRδ repertoires between neonate and adult suggest either peripheral selection of clonotypes responsive to microbial antigens or altered postnatal thymic output of Vγ9Vδ2+ T-cells. Interestingly, some individuals demonstrate private Vγ9Vδ2+ expansions with distinct effector phenotypes, suggestive of selective expansion in response to microbial stimulation. The Vγ9Vδ2+ T-cell subset, therefore, exhibits many features common to mouse γδ T-cell subsets, including early development, a semi-invariant TCR repertoire, and a reliance on butyrophilin-like molecules in antigen recognition. However, importantly Vγ9Vδ2+ T-cells retain TCR sensitivity after acquiring an effector phenotype. We outline a model for Vγ9Vδ2+ T-cell development and selection involving innate prenatal repertoire focusing, followed by postnatal repertoire shifts driven by microbial infection and/or altered thymic output.